Occupational risk factors for relapse-free survival in bladder cancer patients. Issue 22 (1st December 2016) - Selinski, Silvia; Bürger, Hannah; Blaszkewicz, Meinolf; Otto, Thomas; Volkert, Frank; Moormann, Oliver; Niedner, Hartmut; Hengstler, Jan G.; Golka, Klaus
ABSTRACT: The influence of occupational risk factors on bladder cancer development is well investigated. However, studies on the influence on bladder cancer prognosis are rare. Therefore, it was of interest to investigate the time to first relapse in the follow-ups of three case-control series from Dortmund, Neuss, and Lutherstadt Wittenberg, Germany. Relapse-free survival of in total 794 urinary bladder cancer patients (Dortmund 174, Neuss 407, Lutherstadt Wittenberg 213) was derived from medical records. Cox regression models were used to determine the impact of profession and exposure to bladder carcinogens if the risk factor was present in at least four cases. One or several relapses were observed in 416 cases (52%). Median time to first relapse was 0.94 yr. Ten professions were observed in at least 4 patients. No significant associations were found. However, workers in the leather industry ( n = 4), printing industry ( n = 4), transportation ( n = 43), and chemical industry ( n = 40) and locksmiths/mechanics ( n = 44) showed shorter relapse-free times. No trend to shorter relapse-free time was observed for miners ( n = 42), agriculturists ( n = 18), painters/lacquerers ( n = 21), colorant production and processing workers ( n = 7), foundry workers ( n = 5), and persons exposed to aromatic amines ( n = 45). Although the follow-up comprised nearly 800 cases, data on occupations and exposures of interest were not sufficient to obtain significant results. However, first results indicated potential associations that are worth further investigations.